Ovarian Cancer: A Clinical Challenge That Needs Some Basic Answers - Lawrenson, Kate (Public Library of Science, 2009)
Kate Lawrenson and Simon Gayther discuss two studies of ovarian cancer inPLoS Medicine, one on clinico-pathological heterogeneity and one on gene expression profiling.